THE LEGAL CONSTRUCTION OF CHILD CUSTODY IN THE LAHAT RELIGIOUS COURT: AN ANALYSIS OF CUSTODY AWARDS TO FATHERS AFTER DIVORCE - Islami, Muhammad Zhamir; Hasan, KN, Sofyan Hasan; Mahfuz, Abdul Latif Mahfuz; Masuwd, Mowafg Abrahem Masuwd (Universitas Islam Indonesia, 2025)
Purpose: This study aimed to analyze the legal considerations and implementation of custody decisions in Case Number 977/Pdt. G/2022/PA.LT at the Lahat Religious Court. Specifically, it seeks to examine the legal basis used by the judge in granting custody to the father and evaluate how the decision has been implemented. Methods - A normative-empirical research method is employed, which combines legal analysis with field research. Data were collected through structured interviews with the parties involved and library research on relevant legal sources. This study adopts a qualitative approach with descriptive analysis to interpret judicial reasoning and assess the ruling’s impact. Findings - The judges prioritized the best interests of the child over Article 105(a) of the Compilation of Islamic Law, which normally grants custody of a non-mumayyiz child to the mother. The decision was based on three key considerations: the child had been continuously cared for by the father since the separation, the child expressed a preference to remain with the father, and the mother admitted infidelity as a factor in the divorce. The ruling has been partially effective: while the child remains in the father’s custody, the mother’s visitation rights have been hindered by parental conflict. Over time, however, the child’s initial reluctance to meet the mother shifted toward more positive interactions. Contribution/Limitation: This study contributes to the discourse on custody disputes by demonstrating how judicial discretion and social dynamics influence the application of family law. A limitation of this research lies in its focus on a single case, which may not fully represent broader judicial trends. Originality/Value - The originality of this study lies in its combination of legal and empirical perspectives, offering insights into how custody rulings are not only legally grounded but also shaped by practical, social, and familial considerations.